Servant leadership: A meta-analytic examination of incremental contribution, moderation, and mediation - Lee, A.; Lyubovnikova, J.; Tian, Amy; Knight, Caroline (2019)
© 2019 The British Psychological Society Research suggests that when leaders, as servant leaders, focus on their followers’ needs, this can have a positive effect on organizational functioning. Yet results are inconsistent in establishing the strength of the relationships, limiting understanding of the theoretical impact and practical reach of the servant leadership (SL) construct. Using a quantitative meta-analysis based on 130 independent studies, the current research provides evidence that SL has incremental predictive validity over transformational, authentic, and ethical leadership. Further, the link between SL and a range of individual- and team-level behavioural outcomes can be partially explained by trust in the leader, procedural justice, and leader–member exchange. The paper also explores moderators to better establish SL's criterion-related validity and to clarify the magnitude of effects across boundary conditions, such as research design, national culture, and industry. Practitioner points: Servant leadership has predictive validity over other leadership approaches, and therefore, organizations would benefit by developing their current leaders into SLs. Organizations should aim to select SLs into influential positions: Training programmes and selection profiles and processes would need to be aligned and developed to capture attitudes and behaviours associated with SL inside and outside the organization. Servant leaderships should seek to create a culture that positively promotes the development of trust, fairness, and high-quality leader–follower relationships, as these conditions collectively enable the effects of SL to be transmitted onto desirable follower outcomes.